Analysis of the Organization’s Activity on the Example of the Mckinsey Matrix. Theoretical-Experimental Approach - Yeritsyan, Hovhannes (Bulletin of Yerevan University G: Economics, 2025)
Due to resource constraints, a company cannot cater to all potential markets worldwide in a manner that satisfies all clients and achieves business goals. Therefore, it becomes important for the company to carefully select the most appropriate markets. Given the plethora and diversity of available markets, analyzing market attractiveness and selecting the most promising ones becomes a complex process. The General Electric Matrix, also known as the McKinsey Matrix, employs two dimensions-market attractiveness and competitive strength of the firm-to analyze a company’s strengths and weaknesses across various areas. The matrix aims to help the company identify the most appealing markets, guiding managers in resource allocation and enabling them to enhance the firm’s weaker competitive positions in emerging markets or withdraw from less attractive markets. This tool proves highly effective for international market specialists, aiding in the selection of foreign markets for the company and determining the internationalization strategy to be employed in those markets. This paper concludes with a segment of a broader study showcasing how the General Electric Matrix/McKinsey is specifically utilized in the process of selecting markets. The author used a matrix as an example of a case study, as a result of which the position of a separate portfolio in the market was analyzed and the necessary strategy was proposed for each portfolio.